TURKESTAN JADIDISM IN FOREIGN SCHOLARSHIP (SCIENCE TIME JOURNAL, 2026)
This article provides a comprehensive analysis of the study of Jadid literature in foreign scholarship, with particular attention to the works of Jeff Sahadeo. The research examines Sahadeo’s scholarly interpretations of the Russian Empire’s colonial policy in Turkestan, the local society, and the Jadid movement. The article highlights his views on colonialism, modernization, national identity, and intellectual resistance within the context of Turkestan's historical development.